An analysis of technical assistance providers in Copanch'orti' Guatemala - LeBeaux, Victoria Samantha (2015)
Guatemala has the fourth highest rate of chronic under-nutrition for children under five in the world. One region particularly impacted is the Copanch’orti’ area of eastern Guatemala where chronic under-nutrition affected 61% of the population in 2008. Although efforts to solve the malnutrition problem have been underway for several decades, there is a persistent need for greater and better coordination and integration of food security programming, within and across sectors (agriculture, education, environment, health, etc.), as well as across local, regional, and national platforms. In this dissertation I addressed the question of how the actions of development practitioners can be better coordinated to result in cumulative successes in regional food security. I addressed this question through a joint application of the community capitals framework and the agency theory of incentives to empirical data collected from a diverse group of development organizations working to enhance food security for rural, farming households in the Copanch'orti' region of eastern Guatemala. Findings reveal that systemic barriers to change exist in the form of a lack of incentives for investments in long-term improvements that would challenge existing power structures that allow inequalities to persist among the poorest groups. Future research should seek to gather in-depth information from a wider range of actors including citizens' groups and funding agencies to better identify mechanisms that will advance the region’s food security goals.